As condições de trabalho do intérprete de libras e o reflexo no ensino de surdos - Silva, Douglas Fernando da (2019)
Investigates the Sign Language Interpreter (SLI) working conditions within the educational context and the influences both on simultaneous interpreting (SI) and on education for the deaf, by questioning: how does the simultaneous interpreting process take place in the educational context? How can the SLI working conditions influence in deaf education? What does the SLI think about the relationship between the duration of SI and educational practices? The research questions are established in order to meet the following specific objectives: Analyze the impact of working conditions on interpretative processes and on education; Identify what are SLI’s perceptions about the way in which the duration of interpreting interfere on work quality; Discover the conditions under which the SLI is working in Brazil and its consequences. From Gile’s (2015) Effort Models, develops the hypothesis that the SLI’s exposition to inappropriate working conditions associated to a long period of simultaneous interpreting, compromises the interpreting quality and the education. Submits an electronic questionnaire hosted in the application of research administration Google Forms and propagated it through electronic media (Whatsapp and Facebook), to be answered by SLI that work/have worked in educational contexts, regardless of level that they work/have worked on; and that was answered by 179 subjects. Identifies that the SLI provokes a modification in the speech circuit, originally proposed by Saussure (2002). Concludes that inappropriate working conditions are directly connected to the decay of the SI product, leading to the occurrence of Repetitive Strain Injury (RSI)/Osteomuscular Work-Related Disease (OWRD) in SLI, and the more working years, the more these professionals are affected by these diseases. Also identifies that RSI/OWRD is more likely to occur in those SLI that undertake increased weekly working hours, which is 8% (eight percent) higher in the group of SLI that work in the higher education context.